A further evaluation of the sperm length in aleocharines (Coleoptera Staphylinidae) - Luigi De Marzo (Journal of Entomological and Acarological Research, 2010)
and maximum values are respectively 100 μm for Aleochara intricata Mannerheim and 3.000 μm for Heterota plumbea (Waterhouse). E valuations for most species were carried out either on spermatozoa separated from the spermatheca or on bundles extracted from testes. Sperm length of Atheta inquinula was supposedly assumed as corresponding to that of the vasa deferentia. Conclusive diagrams show sperm length in some species to be disproportionate if compared with the size of the receptacle.